Structural, Surface and Catalytic Properties of Nano-Sized Ceria Catalysts - N.M. Deraz; A. Alarifi (Adsorption Science & Technology, 2009)
Well-dispersed uniform spheres of crystalline CeO 2 were prepared by calcining precursor particles obtained by heating ammonium cerium nitrate for 4 h. These spherical substrates were examined using XRD and TEM methods, and by nitrogen adsorption studies at −196 °C. Subsequently, such cerium oxide particles prepared by calcination at 400–600 °C were used as catalysts for the conversion of isopropanol at 250–450 °C, using a flow method. The results obtained showed that increasing the heating temperature of the system investigated from 400 °C to 600 °C stimulated the formation of a well-crystallized CeO 2 phase having a crystallite size varying between 10 and 20 nm. Both the surface area and catalytic activity of cerium oxide were found to decrease on increasing the calcination temperature. All solids investigated behaved as dehydrogenation catalysts which were selective towards the formation of acetone. The heat treatment did not alter the mechanism of dehydrogenation of isopropanol, but changed the concentration of active sites involved in the catalyzed reaction without altering their energetic nature.